Oxidative behavior of (+)‐catechin in the presence of inactive dry yeasts: a comparison with sulfur dioxide, ascorbic acid and glutathione. (6th June 2017) - Comuzzo, Piergiorgio; Toniolo, Rosanna; Battistutta, Franco; Lizee, Marion; Svigelj, Rossella; Zironi, Roberto
Abstract: BACKGROUND: The antioxidant capacity of an inactive dry yeast preparation (YD) was investigated by conventional analytical methods (spectrophotometry, high‐performance liquid chromatography) as well as by cyclic voltammetry in a (+)‐catechin model wine and compared with that of some of the most common antioxidants found in wine: sulfur dioxide, ascorbic acid and glutathione. RESULTS: Sulfur dioxide was the highest‐performing substance in protecting (+)‐catechin against browning, followed by ascorbic acid and the YD preparation. Sulfites were the only antioxidant whose activity was clearly detectable in the model wines after 29 days of storage. Voltammetric studies demonstrated that the antioxidant capacity of the products tested was connected to their intrinsic characteristics and their molar concentrations (catechin/antioxidant molar ratio). CONCLUSION: The YD preparation displayed a certain ability to protect polyphenols against browning. The antioxidant activity of YDs towards (+)‐catechin appeared to be based on different mechanisms with respect to that of the other products tested: the insoluble portion of these preparations (cell wall residues) might have a non‐negligible role, even if the ability of YDs to release compounds able to suppress oxidation cannot be rejected. Direct comparison of the different antioxidants led to interesting indications concerning their mechanism of action in wine‐like solution, depending on their concentration and intrinsic characteristics. © 2017 Society of Chemical Industry